Urinary incontinence during pregnancy: prevalence, experience of bother, beliefs, and help-seeking behavior - Moossdorff-Steinhauser, Heidi F. A. (Int Urogynecol J, 2020)
INTRODUCTION AND HYPOTHESIS: Pregnancy and delivery are thought to induce urinary incontinence (UI), but its clinical impact is less known. Therefore, we investigated the prevalence of self-reported UI, level of experience of bother, and beliefs to gain a greater understanding of help-seeking behavior in adult pregnant women. METHODS: A digital survey shared on social media was used for recruitment. The survey consists of: (1) demographic variables, (2) International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF), (3) ICIQ Lower Urinary Tract Symptoms Quality of Life (ICIQ-LUTSqol), and (4) questions on beliefs and help-seeking behavior. For analysis, descriptive statistics and the independent samples t-test were used to determine differences between help- and non-help-seekers. RESULTS: Four hundred seven women were eligible for data analysis. The prevalence of UI rises from 55.1% in the first to 70.1% in the third trimester, with an overall prevalence of 66.8%. Nearly 43.0% of the respondents reported UI occurring once a week or less; 92.5% of women lost a small amount; 90% reported slight to moderate impact on quality of life. Only 13.1% of the respondents sought help for their UI. The main reasons for not seeking help were: minimal bother and the idea that UI would resolve by itself. Help-seeking women showed significantly higher scores than non-help-seeking women regarding ICIQ-UI SF (p < 0.001), ICIQ-LUTSqol (p ≤ 0.001), and interference in daily life (p < 0.001). CONCLUSIONS: During pregnancy, UI affects two out of three women, but only one in eight women sought professional help. Non-help-seeking women experience less bother.